A Study of Work Values of Secondary School Teachers in Relation to Organisational Culture - C., Jose C. (JOURNAL OF INDIAN EDUCATION, 2012)
In recent years, interest among researchers in the study of work values and their correlates in understanding the functioning of organisation is gaining importance. It was intended through the present investigation to study the work values of secondary school teachers in relation to organisational culture. Based on a survey, the sample constituted 172 secondary school teachers belonging to Christian schools in Bangalore. The data were analysed using correlation and t–test techniques. Results indicated significant relationship between work values of secondary school teachers of Christian schools with organisational culture. Further there were significant differences between male and female teachers; teachers of type of Christian Denominations with respect to (catholic and others) and (protestant and others) of secondary school of Christian schools differ significantly with respect to organisational culture. Implications in the light of empowering educational leaders and suggestions for further research are discussed.